Bortezomib modulates CHIT1 and YKL40 in monocyte-derived osteoclast and in myeloma cells - Tibullo, Daniele; Di Rosa, Michelino; Giallongo, Cesarina; La Cava, Piera; Parrinello, Nunziatina L.; Romano, Alessandra; Conticello, Concetta; Brundo, Maria V.; Saccone, Salvatore; Malaguarnera, Lucia; Di Raimondo, Francesco (Frontiers in Pharmacology, 2015)
Osteolytic bone disease is a common manifestation of multiple myeloma (MM) that leads to progressive skeleton destruction and is the most severe cause of morbidity in MM patients.It results from increased osteolytic activity and decrease osteoblastic function. Activation of mammalian chitinases CHIT1 and YKL40 is associated with osteoclast (OCs) differentiation and bone digestion. In the current study, we investigated the effect of two Bortezomib’s concentration (BO) (2.5 nM and 5nM) on osteoclastogenesis by analyzing regulation of chitinase expression. OCs exposition to BO was able to inhibit the expression of different OCs markers such as RANK, CTSK, TRAP and MMP9. In addition BO-treatment reduced CHIT1 enzymatic activity and both CHIT1 and YKL40 mRNA expression levels and cytoplasmatic and secreted protein. Moreover, immunofluorescence evaluation of mature OCs showed that BO was able to translocate YKL40 into the nucleus, while CHIT1 remained into the cytoplasm. Since MM cell lines such as U266, SKM-M1 and MM1 showed high levels of CHIT1 activity, we analyzed bone resorption ability of U266 using dentin disc assay resorption pits. Silencing chitinase proteins in U266 cell line with specific siRNAs, resulted in pits number reduction on dentine discs. In conclusion, we showed that BO decreases osteoclastogenesis and reduces bone resorption in OCs and U266 cell line by modulating the chitinases CHIT1 and YKL40. These results indicate that chitinases may be a therapeutic target for bone disease in MM patients.